Prevalence of Chronic Kidney Disease and Its Risk Factors in Gonabad, Iran (Iranian Journal of Kidney Diseases, 2015)
Introduction. Chronic kidney disease (CKD) is an important health problem in Iran, with an increasing prevalence rate. Knowledge about the prevalence and risk factors of this disease in different health jurisdictions can help in planning to control this condition. Materials and Methods. In this cross-sectional study, 1285 individuals aged between 20 and 60 years old were recruited. Participants were selected from the general population residing in Gonabad, Iran, via simple random sampling in 2012. Demographic data were collected. Urine and blood test were performed, and the glomerular filtration rate was estimated based on the simplified Modification of Diet in Renal Disease equation. Results. Sixty-five participants (5.1%) had CKD (5.1% men and 5% women; P = .90). The mean age was significantly higher in the CKD group (P = .001). Hypertension and diabetes mellitus were significantly more prevalent among the participants with CKD than those without CKD (P < .001 for both). Proteinuria was significantly associated with CKD, whereas a history of urinary tract infection, a history of nephrolithiasis, smoking, serum uric acid level, lipid profile, and blood glucose level were not. Conclusions. Chronic kidney disease has a high prevalence rate in this part of Iran. We suggest further studies in other parts of our country for the better estimation of the prevalence of CKD in Iran and for better planning to prevent and treat this condition.